Occupational exposure to organic solvent mixtures during pregnancy and the risk of non-syndromic oral clefts. Issue 9 (27th April 2006) - Chevrier, C; Dananché, B; Bahuau, M; Nelva, A; Herman, C; Francannet, C; Robert-Gnansia, E; Cordier, S
Abstract : Objectives: To examine the association between maternal occupational exposure to mixtures of organic solvents during pregnancy and the risk of non-syndromic oral clefts. Methods: A case-control study (164 cleft lip with/without cleft palate (CL/P), 76 cleft palate (CP), 236 controls) was conducted in France to investigate the role of maternal occupational exposure to organic solvents at the beginning of pregnancy in the risk of non-syndromic oral clefts. An expert chemist, guided by a detailed description of the women's occupational tasks, assessed exposure for each. Analysis of the findings used logistic regression. Results: In the control group, 39% of the women who reported working during pregnancy were exposed to at least one type of organic solvent. The risk of oral clefts was associated with oxygenated (for CL/P: OR = 1.8, 95% CI 1.1 to 2.9; and for CP, OR = 1.4, 95% CI 0.7 to 2.7), chlorinated (OR = 9.4, 95% CI 2.5 to 35.3; OR = 3.8, 95% CI 0.7 to 20.7), and petroleum (OR = 3.6, 95% CI 1.5 to 8.8; OR = 1.2, 95% CI 0.3 to 4.9) solvents. The risk of oral clefts increased linearly with level of exposure within the three subgroups of oxygenated solvents we considered (aliphatic alcohols, glycol ethers, and other oxygenated solvents, including esters, ketones, and aliphatic aldehydes). Conclusions: Results suggest that maternal occupational exposure to organic solvents during pregnancy may play a role in the aetiology of oral clefts. The limited number of subjects and the problem of multiple exposures require that these results be interpreted cautiously.